MANAJEMEN PENDIDIKAN PEMBINAAN ANAK JALANAN - Mundilarno Mundilarno (LPMPP Universitas Negeri Yogyakarta, 2003)
Human resources quality in the future depended onthe quality ofthe young generation now. But in Indonesia since five years later there are men, women, and children work as beggar and or street musician asked for money in the streets. The shortage of the finance ofthe government through and the economic crisis to be predicted as the most importance factor to make the community street problem to be more complicated. However this problems must be overcome iflndonesian would not have the loss generation. Street children can be divided in to four groups ofage: the under 5 years old, primary school age, junior high school age, and senior years school age. We also make the street children in to two groups. The first group consist ofchildren who are stilI as student both in the level ofthe primary school (SD) or junior high school (SLTP) student and a group that consist of no student children. The research ofthe street children problems done along the street of Yogyakarta city. Some information also found by interview with public figure and head office ofsocial department of Yogyakarta province. There are four prime factor, which make boy and girls to be street children that are economic problems, friend influence, forced by parent, and laziness. Basedon this factors some approaches must be considered to overcome the street children problem especially in the perspective of education. The physical aspect ofroad may be made in order mismatch for the lazy group ofstreet children. In other words the physical condition and road situation must be made to make children boring and finance aid ofpeople must be given to street children that caused by economic problems. Skill training programs may overcome the problem ofthe school drop out children. Coordination among institutions especially with the high education institutions must be done to overcome the finance problems and to make the education management of the street children to be systematic. Key words: TheLaziness factor, roads' physical design, educative approach integrated.